Pengolahan Sampah Plastik Menjadi Tas Belanja Serbaguna Bersama Ibu PKK - Oktaviana, Aisyah Nur Widya; Safitri, Mardiana; Adzani, Mutiara Lintang; Tiara, Inka; Eviana Sari, Iin; Putra, Ardian Prima (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
Until now, plastic waste is still a major problem if left unchecked. Plastic waste will certainly have a negative impact on the environment, such as polluting water, air, soil, and clogging waterways, as well as having a negative impact on the health of living things. This is because plastic packaging waste takes a long time to decompose. The purpose of this community service activity is to increase knowledge, skills, and processing plastic waste into multipurpose shopping bags. This service partner is a PKK mother who is in the hamlet of Keblokan RT 03/ RW 08, Sendangijo, Selogiri, Wonogiri, Central Java. The methods used are pre-test, outreach, post-test, training & mentoring, as well as the evaluation stage. As a result of this community service, it is hoped that processing plastic waste into multipurpose shopping bags can have a positive impact on PKK mothers and the environment, and can even become a business opportunity for the community. This community service is beneficial to the community because it can manage useless plastic packaging waste into useful and valuable products.